OPTIMIZATION OF HOSPITAL MANAGEMENT INFORMATION SYSTEM TO SUPPORT MANAGERIAL DECISIONS - Ahmad Syakur Banafif; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of information technology has brought fundamental changes to hospital governance. One strategic instrument that plays a crucial role is the Hospital Management Information System, as regulated in Minister of Health Regulation Number 82 of 2013. SIMRS functions not only as an administrative system but also as a decision support system that provides real-time and integrated data to support managerial decision-making. This study uses a literature review method by analyzing various recent research results related to the implementation and optimization of SIMRS in hospitals. The results show that SIMRS can improve administrative efficiency, accelerate patient data access, strengthen inter-departmental coordination, and facilitate data-driven decision-making. However, several obstacles remain, including high implementation costs, user resistance to change, system complexity, limited cross-module integration, and data security risks. Optimizing SIMRS requires a continuous training strategy for all staff, system adjustments to hospital needs, regular software updates, and close collaboration between the information technology team and medical personnel.